Experiences and Perceptions of Elite Female Athletes of How the Menstrual Cycle Affects Performance and Achievement in Sports Competition in West Java - Senny Sharapova Indrianing; Widiawati, Prisca; Ramadhan, Muhammad Putra (Indonesian Journal of Sport Management, 2025)
ABSTRACT Background: Menstruation can be one of the obstacles for athletes in each sports activity because female athletes who have periods can still take part in training and matches. This perspective can cause discrimination and a lack of understanding of the female athlete’s condition. Objective: This study aims to find out the experiences and perceptions of elite female athletes of how the menstrual cycle affects performance and achievement in sports competitions in West Java. Method: This study used a non-experimental quantitative approach. Data were collected through the survey method. Population in this study was female athletes who have experienced a menstrual cycle from various sports in West Java Province. The number of populations was 219 elite female athletes. The instrument in this study used a questionnaire obtained from a sample of female athletes. Results: The characteristics of respondents' periods showed that average athletes experienced an irregular menstrual cycle and felt pain with different pains. Even though athletes felt pain, they did not consume hormonal contraceptive pills. Most athletes were not affected by the menstrual cycle during training, although during competition, the performance of athletes was sometimes influenced by the menstrual cycle. Many athletes do not communicate about menstrual problems, and many coaches and teams do not change their training patterns during the menstrual cycle. Conclusion: Based on the results of the study, it can be concluded that the average performance and achievement of female athletes in West Java during the menstrual cycle are different or decreased. Implication: Female athlete training programs must be adjusted to the menstrual cycle to optimize their performance.